Comparative Analysis of Budgetary Indicators of European Municipal Subsystems in the Post-Crisis Term between 2009–2018 - Hegedűs, Szilárd; Lentner, Csaba (Public Finance Quarterly, 2020)
The aim of our research was to analyse trends in the fiscal indicators of municipalities in the countries of the European Union and the European Economic Area. To that end, we examined the municipal fiscal indicators between 2009 and 2018 across 31 European countries that report regularly to Eurostat. In our research, we sought answers to three main yet related research questions. Ad 1. How has the crisis affected the operation of European municipal systems? Ad 2. In which way has it influenced the different groups of countries defined in public law and European regional context? Ad 3. How did the characteristics of the local authorities governed by public law changed, that is, how did the classical system characteristics change evaluated by fiscal indicators in the light of the crisis and the crisis management measures made in response to it? We used methods of descriptive statistics, as well as cluster analysis and variance analysis to verify our hypotheses. In our study, we concluded that the crisis has made a significant impact on local government fiscal indicators, however, it had a different impact on the post-Soviet region, the Mediterranean region and the Scandinavian countries. The Rhine (public law) model has proved to be the most crisis-resistant. It has been proved that the specifics described by fiscal indicators do not fully correspond to the municipal system models under public law. At the end of our research, the characteristics of the Hungarian local governmental system following the municipal reform were presented.